Preservation Politics: Keeping Historic Districts Vital - Schmickle, William E. (Rowman & Littlefield Publishers, 2012)
You’ve established a historic district in your town! Now what? Preservation Politics picks up where The Politics of Historic Districts leaves off, advising the established HPC on how to maintain momentum in their communities once the initial political campaign to win historic preservation designation has faded and the real work of enforcement begins. Schmickle goes beyond “best practices” to get to the political root of our district problems: a collective preference for putting preservation interests ahead of citizens and the larger public good. He argues that public service is the key to the long-term vitality of historic districts. Along the way, he takes on everyone who threatens district operations, from those who shirk responsibility and shred historic resources to those preservationists whose radicalism undermines public support. With wit and wisdom, this book shows that there may be no such thing as happily ever after, but historic preservation is worth the fight!